Cover, Editorial Board, Foreword, Table of Content: Metaphor Vol. 4 No. 1 September 2021 - Latifah Dwi Ariyani (Metaphor, 2021)
Cover, Editorial Board, Foreword, Table of Content: Metaphor Vol. 4 No. 1 September 2021